KEDUDUKAN IMAM DESA SEBAGAI AMIL ZAKAT DALAM PERSPEKTIF HUKUM SYARIAH : The Position of Village Imam as Amil of Zakat in Aceh Perspective Syariah Low - Januddin, Januddin (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2023)
In the concept of sharia economics, the distribution of zakat that is evenly distributed and on target is one of the efforts in economic equality to minimize the poverty rate in Aceh in particular. This function is integrated into the role played by Amil zakat as zakat manager including the village priest. This study aims to determine the role of village faith as amil zakat from the perspective of Syariah Low then the legal basis for the prohibition of village priests from receiving zakat in a position as a zakat senior. The method used is a case study by collecting data through in-depth interviews which are analyzed using a qualitative approach. The results of the study presume that the village priest ex officio serves as the head of the BMG so that he has the status of an amil in accordance with article 13 paragraph 4 of Qanun Aceh No 10 of 2018. So the delivery of zakat through the village priest is the same as giving it to mustahik. Even though he has the status of an amil, even so the position of village priest is not that of an amil senior. This is because the village priest is considered a wali iqlim, that is, a person in charge of religious affairs in an area, from this position it is determined that the village priest is not entitled to receive zakat but because of his position as amil, he is entitled to receive only ujrah mitsil from his work in managing.